Sleep apnoea and endothelial dysfunction: An individual patient data meta-analysis. (August 2020) - Bironneau, Vanessa; Tamisier, Renaud; Trzepizur, Wojciech; Andriantsitohaina, Ramaroson; Berger, Mathieu; Goupil, François; Joyeux-Faure, Marie; Jullian-Desayes, Ingrid; Launois, Sandrine; Le Vaillant, Marc; Martinez, Marie-Carmen; Roche, Frédéric; et al.
Summary: We performed an individual patient data meta-analysis to investigate the association between obstructive sleep apnoea (OSA) severity and the reactive hyperaemia index (RHI) measured by peripheral arterial tonometry (PAT), a validated measurement of endothelial function, and a strong predictor of late cardiovascular (CV) events. Patients from 12 studies underwent PAT and overnight polysomnography or respiratory polygraphy for suspected OSA. Endothelial dysfunction was defined by a log-transformed RHI<0.51. Subgroup analyses were performed to investigate this relationship in specific populations. Among 730 patients without overt CV disease, 387 (53.0%) had severe OSA (apnoea-hypopnea index ≥30) and 164 (22.5%) exhibited endothelial dysfunction. After adjustment for age, gender, diastolic blood pressure, obesity, diabetes and chronic obstructive pulmonary disease, endothelial dysfunction was associated with severe OSA (odds ratio, OR [95% confidence interval]: 2.27 [1.12–4.60]; p = 0.02), and nocturnal hypoxemia defined by >20 min with oxygen saturation <90% (OR: 1.83 [1.22–2.92]; p = 0.004) or mean oxygen saturation <92% (OR: 1.52 [1.17–1.96]; p = 0.002). On subgroup analyses, the association between severe OSA and endothelial dysfunction was not significant in patients with hypertension, obesity and/or diabetes. Among adults without overt CV disease, severe OSA is independently associated with an increased risk of endothelial dysfunction that may predispose to late CV events.